Health-related Quality of Life and Domain-specific Associated Factors among Patients with Type2 Diabetes Mellitus in South India (The Review of Diabetic Studies, 2022)
OBJECTIVE: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder that has a major impact on health-related quality of life (HRQOL). The economic burden of the disease, along with its complications, negatively impact the individual, family, and society of Indian diabetic patients. This study explored the perception of the diabetic HRQOL of South Indian type2diabetic patients. METHODS: This study was a cross-sectional descriptive quantitative study conducted in a tertiary care hospital in Chennai, Tamil Nadu, South India. Using the simple random sampling technique, we collected data from 352 T2DM patients aged ≥ 30 years of age who were diagnosed for a minimum of one year. Data collection occurred from June to August 2017. Data were analysed using IBM SPSS, Version 22. RESULTS: Overall, 90% of patients with T2DM perceived poor HRQOL. The total and the domainspecific mean scores of HRQOL were high indicating poor HRQOL in energy mobility, diabetes control, anxiety and worry, social burden, and sexual functioning domains. Being female, increasing age, lower education levels, lower family income, and uncontrolled fasting blood glucose levels predicted poor HRQOL of patients with T2DM. CONCLUSIONS: T2DM impacted the HRQOL in all measured domains of participants. A patient-centred approach to diabetes management can be incorporated to improve or enhance the health-related quality of patients’ lives. Improved HRQOL also may lead to fewer hospitalizations, and hence, reduce healthcare costs.